As faces do corredor cultural de Mossoró-RN: cenários e práticas sociais - Gomes Neto, José (2013)
This work aims to understand the ways in which the social practices and the scenery within a public space located at the city centre of Mossoró - RN, named `The Cultural Corridor` , are constructed. The public space in question will be looked at and analyzed considering it`s components and specificities that, in relation to each other, work as a `public scenario`. The concept of `scenario` is the key for explaining the human actions in the physical space, that is, in the Cultural Corridor. This work also discusses about the action of the public in general and the political groups, and their relationship, within the context of the social practices related to the use of the Cultural Corridor`s space